ANALISIS PENGARUH STRES KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVINIG PADA PT.PERUSAHAAN GAS NEGARA (PERSERO) MEDAN - Hery Syahrial; Della Robica (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2014)
The research of problem are stress of work can influenacejob performance  with work motivation as intervining variable. The method of data collection are questionare and study of documentations. The model of data analysis used are Structure Equation Modelling (SEM). The determination of sample using  Slovin formula and the writer used the accidental sampling, the total samples were 48 workers. The results of this study indicate work stress indirectly affect performance but through previous job satisfaction variables.